Using best practices in designing a lifelong learning strategy for human resources in Romania - Dorel Mihai Paraschiv; Radu Stoika (Amfiteatru Economic Journal, 2013)
Starting from the understanding that society as a whole can not move forward without sufficient incentives, we initiated this research aiming to identify good practices in formulating strategies on lifelong learning in order to emphasize the need to create a stable framework for the development and training of human resources. Considering that in the last decade there has been a growing desire among higher education graduates to study abroad after their mobility period and showed the willingness to engage in the labor market in other european countries, we think that the proposed research theme fully justify its relevance, in terms of the need to create medium and long term strategies in order to ensure compliance with the next european regulations framework and a set of elements that have the capacity to regain the qualified romanian human resources employed abroad. Without a european workforce that is able to respond promptly to training tasks throughout life, Romania and after that Europe will not gain the skills needed to achieve an competitive advantage among other world economies. In this respect, we think that the present theme is sufficiently anchored in the realities of our contemporary society on the one hand and on the other hand requires to identify the concrete measures that could be put in place in order to improve the issues presented.
Keywords: J21; J24; 330; lifelong learning; human resource; good practice; labour market